The between-week reliability of neuromuscular, endocrine, and mood markers in soccer players and the repeatability of the movement demands during small-sided games - William Sparkes (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Establishing the reliability and repeatability of both the movement demands and the consequential responses of athletes applied settings is important. Therefore, the primary aim of this study was to assess the between-week reliability of potential fatigue monitoring methods in soccer players. Secondary aims were to establish the repeatability of the movement demands and the changes in monitoring variables from the same small-sided game (SSG) protocol programmed on consecutive weeks. METHODS: Twelve semi-professional soccer players (age, 21±2 years; mass, 80.1±6.8kg; height, 1.81±0.06m) performed the same SSG protocol (4vs4+goalkeepers; 6x7-min, 2-min inter-set recovery) separated by 7 days. Movement demands were monitored using global positioning systems (GPS), with countermovement jump (CMJ), saliva (testosterone and cortisol), and brief assessment of mood (BAM+) collected immediately pre and post SSG training. RESULTS: Results suggest that CMJ variables and hormonal markers have good between-week reliability when measuring athletes at rest (CV, 2.1–7.7%; ICC, 0.82–0.98), however BAM+ did not (CV, 23.5%; ICC, 0.47). GPS variables presented low to high repeatability during SSG training, with reliability statistics varying between metrics (CV, 4.4–62.4%; ICC, 0.30–0.81). In detecting responses from pre- to post-SSG training, CMJ and hormonal markers showed moderate to very-high reliability (ICC, 0.68–0.99), whilst BAM + did not (ICC, 0.12). CONCLUSIONS: The findings from this study suggest CMJ and hormonal markers provide good between-week reliability, yet caution should be applied when using short subjective questionnaires. Additionally, some movement demands may not be repeatable when programming the same SSG session on separate occasions.